The new Wittgenstein - Crary, Alice, 1967-; Read, Rupert J., 1966- (Routledge, 2000)
A stellar collection of essays that presents a significantly different portrait of Wittgenstein and sheds light on the relation between his thought and different philosophical positions and areas of human concern.